"Propre en grant biauté": Das wunderschöne Ross, das die umfangreiche Liebe darstellen soll - Majorossy, Imre Gábor (Verbum – Analecta Neolatina, 2015)
The essentials of the courtly short story cannot be found merely in the history, but in the extraordinary main character who personifies the abstract idea of Love. The fact itself that it is impossible to capture the subsistence of the horse creates a similarity to love that underlies all the events, and significantly characterizes the whole story. The position of marriage comes to light in an unavoidable change which causes a serious crisis. Only by the help of the wonderful horse is it possible to find a solution to the almost hopeless situation. The short story proposes a sort of compromise for such crises that are expected to arise by the occasion of changes of power. The poetic message equals an example how to avert the tragic conflict and how to carry out the change within the meaning of Christianity, in favour of love.